Distinct epidemiology and resistance mechanisms affecting ceftolozane/tazobactam in Pseudomonas aeruginosa isolates recovered from ICU patients in Spain and Portugal depicted by WGS. (25th October 2020) - Hernández-García, Marta; García-Castillo, María; García-Fernández, Sergio; Melo-Cristino, José; Pinto, Margarida F; Gonçalves, Elsa; Alves, Valquíria; Vieira, Ana Raquel; Ramalheira, Elmano; Sancho, Luísa; Diogo, José; Ferreira, Rui; et al.
Abstract: Objectives: To analyse the epidemiology, the resistome and the virulome of ceftolozane/tazobactam-susceptible or -resistant Pseudomonas aeruginosa clinical isolates recovered from surveillance studies in Portugal (STEP, 2017–18) and Spain (SUPERIOR, 2016–17). Methods: P. aeruginosa isolates were recovered from intra-abdominal, urinary tract and lower respiratory tract infections in ICU patients admitted to 11 Portuguese and 8 Spanish hospitals. MICs were determined (ISO-standard broth microdilution, EUCAST 2020 breakpoints). A subset of 28 ceftolozane/tazobactam-resistant P. aeruginosa isolates were analysed and compared with 28 ceftolozane/tazobactam-susceptible P. aeruginosa strains by WGS. Results: Clonal complex (CC) 235 (27%) and CC175 (18%) were the most frequent, followed by CC244 (13%), CC348 (9%), CC253 (5%) and CC309 (5%). Inter-hospital clonal dissemination was observed, limited to a geographical region (CC235, CC244, CC348 and CC253 in Portugal and CC175 and CC309 in Spain). Carbapenemases were detected in 25 isolates (45%): GES-13 (13/25); VIM type (10/25) [VIM-2 (4/10), VIM-20 (3/10), VIM-1 (2/10) and VIM-36 (1/10)]; and KPC-3 (2/25). GES-13-CC235 (13/15) and VIM type-CC175 (5/10) associations were observed. Interestingly, KPC-3 and VIM-36 producers showed ceftolozane/tazobactam-susceptible phenotypes. However, ceftolozane/tazobactam resistance was significantly associated with GES-13 and VIM-type carbapenemase production. Six non-carbapenemase producers also displayed ceftolozane/tazobactam resistance, three of them showing known ceftolozane/tazobactam resistance-associated mutations in the PBP3 gene, ftsI (R504C and F533L). Overall, an extensive virulome was identified in all P. aeruginosa isolates, particularly in carbapenemase-producing strains. Conclusions: GES-13-CC235 and VIM type-CC175 were the most frequent MDR/XDR P. aeruginosa clones causing infections in Portuguese and Spanish ICU patients, respectively. Ceftolozane/tazobactam resistance was mainly due to carbapenemase production, although mutations in PBP-encoding genes may additionally be involved.